Upaya Peningkatkan Kesadaran Masyarakat melalui Skrining dan Edukasi Defisiensi Vitamin D di Danau Sunter - Alexander Halim Santoso; Muhammad Rifat Umar Alwini; Kenzie Rafif Ramadhani (Pusat Riset dan Inovasi Nasional, 2025)
Vitamin D deficiency is a condition that often goes unnoticed but has widespread health implications, particularly among the adult population. Through this community service activity, vitamin D levels were screened in 49 adult participants in the Danau Sunter area using serum 25(OH)D testing, accompanied by education on the importance of vitamin D, its natural sources, and strategies for preventing deficiency. The results showed variation in vitamin D levels among participants, with a mean of 59.13 ng/mL and a range of 26.6–91.8 ng/mL. A total of 3 participants (6.12%) were found to have vitamin D deficiency. Several individuals were identified as being in the deficiency category, requiring further intervention. The educational component played an important role in increasing participants’ awareness and understanding of the role of vitamin D in preventing musculoskeletal and metabolic complications. This program successfully identified individuals in the community with vitamin D deficiency and improved knowledge regarding its prevention. Keywords: Early Detection, Deficiency, Vitamin D